2015
DOI: 10.1002/rob.21572
|View full text |Cite
|
Sign up to set email alerts
|

Rotation Identification in Geometric Algebra: Theory and Application to the Navigation of Underwater Robots in the Field

Abstract: We report the derivation and experimental evaluation of a stable adaptive identifier to estimate rigid body rotations using rotors in Geometric Algebra (GA). This work is motivated by the need for in situ estimation of the alignment between sensors commonly used in underwater vehicle navigation. Here we derive an adaptive identifier using a geometric interpretation of the error to drive first-order rotor kinematics. We prove that it is Lyapunov stable, and we show that it is asymptotically stable in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
(133 reference statements)
0
7
0
Order By: Relevance
“…This fact is supported by Euler's rotation theorem 44 . Although its existence in matrix algebra has been known since Euler's time, its realization is really tedious and is not free of several inconveniences, 37,45,46 although some optimized implementations exist, such as those of Rodrigues 47 . Obtaining the plane and angle of rotation in GA for 3D is determined in a much simpler and more intuitive way, by simply calculating the associated GA rotor 36 …”
Section: Clarke Transformation As a Geometric Manipulation Of Electri...mentioning
confidence: 99%
“…This fact is supported by Euler's rotation theorem 44 . Although its existence in matrix algebra has been known since Euler's time, its realization is really tedious and is not free of several inconveniences, 37,45,46 although some optimized implementations exist, such as those of Rodrigues 47 . Obtaining the plane and angle of rotation in GA for 3D is determined in a much simpler and more intuitive way, by simply calculating the associated GA rotor 36 …”
Section: Clarke Transformation As a Geometric Manipulation Of Electri...mentioning
confidence: 99%
“…Stanway and Kinsey [221] presented the formulation of a stable adaptive identifier to estimate rigid body rotations using rotors in GA. The authors showed an experimental evaluation of this technique, which reduces dead reckoning navigation errors on these platforms and provides comparable performance to previously reported SO(3) constrained Linear Algebra (LA) approaches.…”
Section: Estimation Pose Hand-eye Relocalization Kalman Filtermentioning
confidence: 99%
“…Sound speed, installation error and ocean currents are the main DVL error factors, and most of the DVL errors caused by these factors can be calculated and compensated before DVL velocity output. However, not all DVL velocity errors can be compensated, which means that there is a residual error as the component of DVL velocity output and influence the DVL accuracy [ 36 , 37 , 50 , 51 , 52 ]. It means that the components of DVL output includes the vehicle’s real velocity and the DVL residue error, and the DVL residue error is unclear where it comes from.…”
Section: Principle Of the Integration Subsystem And Error Analysismentioning
confidence: 99%